Characterization of noise reduction capabilities of porous materials under various vacuum conditions. (April 2020) - Huang, Kai; Dai, Liming; Fan, Yurui
Abstract: Noise pollution has been considered as a major challenge for the life of quality and engineering practices for environmental noise control for urban communities is of great importance. In this study, a series of experimental investigations are conducted to investigate the effects of a vacuum on the sound reduction and acoustic properties of porous materials. It is well known that sound cannot be transmitted under a full vacuum. However, a full vacuum condition cannot be realistically achieved in the construction process. Vacuum glass and related products are available in the market but these products can only extract a small degree of vacuum and can hardly withstand atmospheric pressure. Based on current research findings, a porous material with a certain degree of vacuum can achieve better noise reduction. The experimental setups are designed such that various porous materials can be tested, the desired vacuum levels can be maintained, and the ambience noise can be reduced to a sufficiently low level. Laboratory experiments are conducted to measure acoustic responses under various porous materials and vacuum levels. Sound intensities and corresponding frequencies are measured for porous materials with desired vacuum levels. The vacuum in porous materials, even at relatively low vacuum levels, has a significant effect on sound reduction. A vacuum of 10% in glass ball and polystyrene foam can lead to a noise reduction of more than 3 dB. The combination of vacuum and polystyrene foam has a more significant noise reduction effect, which can reach more than 8 dB for 30% vacuum. The research results may contribute to the comprehension of acoustic properties of porous materials under optimal vacuum levels. It is anticipated the research findings may lead to the construction of effective sound reducing products for noise attenuation, increasing insertion loss or improving sound insulation.